Autonomous navigation strategy in quadruped robots for uneven terrain using 2D laser sensor - Silva, Vagner Dos Santos Da; Santos, Marcella Giovanna S. Dos; Vieira, Miguel Felipe Nery; Matos, Victor Santos; Queiroz, Ícaro Nascimento; Lima, Rebeca Tourinho (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Quadruped robots are designed with four legs to enhance stability and maneuverability. Recent advancements in machine learning, computer vision, and control algorithms have enabled these robots to perform complex tasks with increased precision and efficiency. They have proven effective in exploration, military operations, agriculture, search and rescue missions, and can assist in dangerous environments while carrying heavy payloads. This paper aims to address the issue of autonomous navigation in quadruped robots equipped with a 2D laser sensor, which performs well in regular environments but struggles when dealing with uneven terrain such as slopes. To overcome this limitation, a monitoring strategy is implemented to make the 2D navigation independent of the robot’s movement on different terrains.